Genetic testing in intellectual disability psychiatry: Opinions and practices of UK child and intellectual disability psychiatrists. Issue 2 (23rd August 2017) - Wolfe, Kate; Stueber, Kerstin; McQuillin, Andrew; Jichi, Fatima; Patch, Christine; Flinter, Frances; Strydom, André; Bass, Nick
Abstract : Background: An increasing number of genetic causes of intellectual disabilities (ID) are identifiable by clinical genetic testing, offering the prospect of bespoke patient management. However, little is known about the practices of psychiatrists and their views on genetic testing. Method: We undertook an online survey of 215 psychiatrists, who were contacted via the Royal College of Psychiatrist's Child and Adolescent and Intellectual Disability Psychiatry mailing lists. Results: In comparison with child and adolescent psychiatrists, intellectual disability psychiatrists ordered more genetic tests, referred more patients to genetic services, and were overall more confident in the genetic testing process. Respondents tended to agree that genetic diagnoses can help patient management; however, management changes were infrequently found in clinical practice. Conclusions: Differences are apparent in the existing views and practices of child and adolescent and intellectual disability psychiatrists. Developing training and collaboration with colleagues working in genetic services could help to reduce discrepancies and improve clinical practice.